Leveraging AI tools in finance education: exploring student perceptions, emotional reactions and educator experiences - Pamela Córdova; Alberto Grájeda; Juan Pablo Córdova; Alejandro Vargas-Sánchez; Johnny Burgos; Alberto Sanjinés (Cogent Education)
This study explored the integration of Artificial Intelligence (AI) tools in finance education, focusing on student perceptions, emotional reactions, and educator experiences. Quantitative data were gathered using the Synthetic Index of Use of AI Tools (SIUAIT) instrument, administered over three semesters. The findings revealed that finance students perceived AI tools as essential for enhancing their learning experience. Notably, Financial Engineering students exhibited higher proficiency and more positive perceptions of AI tools compared to students in other disciplines, such as Engineering and Business. An observational study utilizing eye tracker technology and facial expression analysis highlighted the emotional dynamics between AI-enhanced and traditional lecture-based classes. Positive emotions, such as joy and surprise, were significantly more prevalent in AI-enhanced environments, contributing to a more engaging and emotionally positive learning experience. However, an increase in fear was also observed, which could be considered a negative activating emotion that, ultimately, still fostered learning. Semi-structured interviews with educators revealed both the opportunities and challenges of AI integration. Educators acknowledged AI’s benefits in enhancing pedagogy but expressed concerns about over-reliance and ethical implications. Thematic analysis identified key dimensions: knowledge, usage, and ethics in AI. The study concluded that AI tools could significantly transform finance education, offering enhanced learning experiences and better preparing students for future careers. However, a balanced approach, addressing ethical and psychological impacts, was essential to maximize benefits and minimize potential drawbacks. Future research should explore AI’s long-term effects and its correlation with academic performance.